Analisis Pembelajaran Bahasa Arab untuk Tujuan Khusus di Era Disrupsi - Lalu Agus Pujiartha; Rizal Firdaus (Rayah Al-Islam, 2025)
Arabic for Specific Purposes (ASP) learning is an important innovation in the development of contemporary Arabic language education, especially in the midst of the demands of globalization and the implementation of the Independent Curriculum. This study is motivated by the need to direct Arabic language learning to be more relevant to specific academic, professional, and social contexts, so that students not only master linguistic aspects, but also be able to communicate effectively in their scientific or professional fields. This study uses a qualitative approach with a library research method sourced from scientific journals and the latest academic literature on ASP. The results of the study show that the success of learning Arabic for special purposes is highly determined by the implementation of needs analysis, the design of relevant curriculum, and the application of task-based learning and content-based instruction. In addition, the integration of digital technology and cross-field collaboration are important factors in increasing the effectiveness and usefulness of ASP in various educational institutions. This study concludes that ASP is able to bridge the gap between Arabic learning theory and the increasingly dynamic needs of the academic and professional world. The relevance of this study lies in its contribution in enriching the discourse on the development of Arabic language education in Indonesia, especially in building a learning paradigm that is contextual, flexible, and competency-oriented in the 21st century. Therefore, the implementation of ASP needs to be made a strategic priority in Arabic language education policies in order to be able to respond to global challenges and strengthen the position of Arabic as a language of science, culture, and international communication.